Plants and their names : a concise dictionary - Hyam, R.; Pankhurst, R. (New York : Oxford University Press, 1995)
Plants and Their Names is the ideal reference for anyone interested in plants and gardening. Over 15,000 entries cover both the scientific and common names of flowering plants, ferns, and conifers - providing a short description of the plant and the origin of its name, the group or family to which it belongs, geographical origin and distribution, and applications in medicinal, culinary, industrial, and other areas. The dictionary concentrates primarily on north temperate plants, but it also includes the better known mosses, algae, and lichens, and tropical plants world-wide.
Keywords: BOTANY -- NOMENCLATURE